2005
DOI: 10.1089/ten.2005.11.618
|View full text |Cite
|
Sign up to set email alerts
|

Mesothelial Cell Sheets Cultured on Fibrin Gel Prevent Adhesion Formation in an Intestinal Hernia Model

Abstract: In the present study, we examined a novel technique to prevent adhesion formation in a rat intestinal hernia model with mesothelial cell sheets cultured on fibrin gel. Mesothelial cells were obtained from isologous rats by enzymatic disaggregation of mesentery and cultured on fibrin gel. Electron microscopy revealed that these cultured cells form contiguous monolayer cell sheets with well-developed microvilli. These tissue-engineered constructs were grafted in vivo to an intestinal hernia model that results in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 27 publications
(24 reference statements)
1
29
0
Order By: Relevance
“…11 Recently, we proposed a new technique for harvesting autologous mesothelial cells from tunica vaginalis without intra-abdominal maneuvers. 16 In the current study, we confirmed the efficacy of autologous mesothelial cell sheet transplantation for preventing post-operative adhesions in a canine adhesion model.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…11 Recently, we proposed a new technique for harvesting autologous mesothelial cells from tunica vaginalis without intra-abdominal maneuvers. 16 In the current study, we confirmed the efficacy of autologous mesothelial cell sheet transplantation for preventing post-operative adhesions in a canine adhesion model.…”
Section: Discussionmentioning
confidence: 99%
“…10 Recently, we reported that transplantation of mesothelial cells cultured on fibrin gel is also effective for preventing adhesions in a rat model. 11 Fibrin gel has been reported to be a reliable and stable material for transplantation and is available clinically. 12,13 We named this tissue-engineered construct composed of mesothelial cells and fibrin gel the ''mesothelial cell sheet.'…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The advent of biological scaffolds associated with MCs and subMCs improve the reconstitution capacity and functioning of the peritoneum and other organs [Takazawa et al, 2005;Sekiguchi et al, 2012;Lachaud et al, 2013;Kitamura et al, 2014;Lachaud et al, 2015]. Considering the anatomic organization, the peritoneal cavity is analogue to a natural bioreactor for tissue engineering of bladder, uterus, and vas deferens [Campbell et al, 2008].…”
Section: Perspectives In Tissue Engineering and Cell Therapiesmentioning
confidence: 99%
“…Recently MC transplantation has been reported to be effective for preventing postoperative adhesions in animal models [5][6][7]. Recently MC transplantation has been reported to be effective for preventing postoperative adhesions in animal models [5][6][7].…”
mentioning
confidence: 99%